Negotiating The Maze: Confronting Dysphagia Together With My Stroke-Afflicted Family Member - Tseng, Ying-Jung; Tsao, Lee-Ing; Wang, Hsueh-Pei; Wang, Vinchi; Chen, Mei-Hui; Wang, Chin-Man; Lin, Shu-Li; Lin, Yu-Li (European Scientific Journal, ESJ, 2016)
Aim: To generate a descriptive theory grounded in the responses of family caregivers caring for their family stroke survivors with dysphagia during hospitalization. Design and Method: A qualitative study employing the grounded theory method was used. Fifteen family caregivers participated in comprehensive interviews. The interview data were analyzed using the constant comparative method. Findings: ‘Negotiating the maze: Confronting dysphagia with my stroke-afflicted family member’ was the core category guiding the care process for dysphagia family members among caregivers. After surviving stroke, the caregivers felt ‘more confusion less rejoicing’ as the antecedent condition. The following three interaction categories were identified: (1) ‘being overwhelmed by nasogastric (NG) tube issues’; (2) ‘searching for the right helper and information’; and (3) ‘food culture conflicts with the formula diet administered through the NG tube’. Additionally, ‘Maintaining positivity’ described the consequence of this process. Conclusions: This study highlights the critical perspective of family members who care for dysphagia stroke survivors in the hospital. Participants were under tremendous pressure during the disease treatment process. However, all attempted to maintain a positive attitude and treasured the chance to accompany their family members. Clinical Relevance: These findings can assist health professionals in charting the effects of dysphagia and in understanding the problems and needs according to the subjective perspectives of family caregivers. They can also provide a necessary foundation for comprehensive care interventions for family caregivers of stroke survivors with dysphagia.